"Covid has Reminded us that Independent Science is Really Important. And Statistics is Part of that" A Conversation with Steve MacFeely. Issue 1 (25th January 2022) - Tarran, Brian
Abstract: Steve MacFeely is director of data and analytics at the World Health Organization, a post he took up in July 2021, during the second year of the coronavirus crisis. In this interview – part of a series highlighting the work of statisticians throughout the pandemic – he discusses the difficulties of measuring the direct and indirect effects of Covid, disruptions and innovations within national statistical systems, and his hopes – and fears – for the future. By Brian Tarran